Tujuh Masalah dalam Praktik Koperasi: Mencari Fakta yang Memberi Harapan - Muhammad Arsad Dalimunte (Universitas Proklamasi 45 Yogyakarta, 2011)
Logically, the cooperative have the rationality to evolve in the future. Yet the development of cooperatives is due to inconsistency in enforcing the identity itself. Because cooperatives are a collection of people, then the core issue of the development of cooperatives lies in the quality of its members. The solution to the problem of human resources in cooperative is education. This article describes two alternative solutions related to human resources education in cooperatives, namely the evolution method and revolution method.